RETRACTED: Assessment of Expression of Regulatory T Cell Differentiation Genes in Autism Spectrum Disorder - Akbari, Mohammadarian; Eghtedarian, Reyhane; Hussen, Bashdar Mahmud; Eslami, Solat; Taheri, Mohammad; Neishabouri, Seyedeh Morvarid; Ghafouri-Fard, Soudeh (Frontiers in Molecular Neuroscience, 2022)
Dysfunction of regulatory T cells (Tregs) has been shown to affect the etiology of autism spectrum disorder (ASD). Differentiation of this group of T cells has been found to be regulated by a group of long non-coding RNAs (lncRNAs). In this study, we have examined expression of five lncRNAs that regulate this process in the blood samples of ASD cases compared with controls. These lncRNAs were FLICR, MAFTRR (MAF Transcriptional Regulator RNA), NEST (IFNG-AS1), RMRP and TH2-LCR. Expression of RMRP was significantly lower in total ASD cases compared with controls (Expression ratio (95% CI)= 0.11 (0.08-0.18), adjusted P value<0.0001). This pattern was also detected in both male and females cases compared with corresponding controls (Expression ratio (95% CI)= 0.15 (0.08-0.29) and 0.08 (0.03-0.2), respectively). Likewise, expression of NEST was reduced in total cases as well as male and female cases compared with corresponding controls (Expression ratio (95% CI)= 0.2 (0.14-0.28); 0.22 (0.12-0.37) and 0.19 (0.09-0.43), respectively; adjusted P value<0.0001). Lastly, FLICR was down-regulated in total cases as well as both boys and girls cases compared with matched controls (Expression ratio (95% CI)= 0.1 (0.06-0.19); 0.19 (0.08-0.46) and 0.06 (0.01-0.21), respectively; adjusted P value<0.0001). These three lncRNAs had appropriate diagnostic power for differentiation of ASD cases from controls. Cumulatively, our study supports dysregulation of Treg-related lncRNAs in ASD patients and suggests these lncRNAs as proper peripheral markers for ASD.